PENGAWASAN KESEHATAN TENAGA KERJA MENURUT PP NOMOR 50 TAHUN 2012 TENTANG PENERAPAN SMK3 - ujang syafrudin (IAIN Syekh Nurjati Cirebon, 2019)
Work accident is one of the problems that exist in the employment sector, for that the government needs to make efforts to minimize work accidents to accommodate workers' rights to protection while working. Occupational Safety and Health management system is one of the efforts made to overcome the problem of work accident. In its implementation so that the Occupational Safety and Health Management System runs well, it is necessary to conduct an oversight. This research aims to illustrate how the implementation of the occupational safety and health management system monitoring functions and the factors that influence the implementation of the supervisory function carried out by the Office of Manpower and Transmigration . Basically, SMK3 supervision is a sub-section of labor inspection carried out by the government, but there is a fundamental difference that lies in the supervision of SMK3 also conducted by auditors of SMK3. SMK3 audits are conducted internally and externally. Internally the audit is carried out by the company / management while the external audit is carried out by the Auditor Board which is conducted at least every 3 years.